Komposisi dan Keanekaragaman Jenis Pohon Di Hutan Lindung Lapeom Kabupaten Timor Tengah Utara - Yolanda Getrudis Naisumu; Yoseph Nahak Seran; Ludgardis Nahak Ledheng (Fakultas Pertanian, Universitas Timor, 2018)
This study aims to describe the composition and diversity of tree species in Lapeom Protection Forests. The study was conducted in November to December 2009 using the quadrat method by plotting along the transect line. The number of transect 5, transect length 200 m, in each transect placed 5 plot with size 20 m x 20 m. The results showed that in the location found 22 species of trees from 17 families. The largest number of species are Caesalpinaceae family of 4 species, was Casia fistula, L, Delonix regia, Rafin, Cassia simea, Lamk, and Tamarindus indica, L. The number of individuals largest is Mangifera indica, L from Anacardiaceae family of 20 individuals. The highest important value index on the species Mangifera indica (43.7%), the species with the lowest important value index was Zizipus jujuba (1.8%,) and Jatropa Sp (1.9%). Index Diversity of tree species in lapeom protected forest including moderate category with a value of 2.7 this showing that the area of Lapeom protected forest an area that has sufficient tree productivity levels, ecosystem conditions that are sufficiently balanced and have an ecological pressures medium. concluding was there are 22 species of tree from 17 families. The species with the highest number of individuals is Mangifera indica, L from Anacardiaceae family. The species that has the highest important value index is Mangifera indica (43.7%) and the species has the lowest important value index is Zizipus jujuba (1.8%), Index diversity of tree species in Lapeom protected forest including medium category.